Influence of r.f power on structural properties of ZnO thin films - Duygulu, N. Evcimen; Kodolbas, A. O.; Ekerim, A. (ELSEVIER SCIENCE BV, 2013)
ZnO thin films were deposited on glass substrates by r.f. magnetron sputtering at room temperature. The dependence of electrical, structural, and optical properties on the r.f. power variations in the range of 150W to 175W was investigated. Structural examinations were done with the help of X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). The achieved results revealed that the films were (002) oriented and at 165W r.f. power the texture reached to a maximum. According to HRTEM, the formation of grains was observed as columnar with nano-islands inside. Also, morphological investigations were carried out using both high resolution scanning electron microscopy (HRSEM) and atomic for cemicroscopy (AFM). The achieved data exhibited that after r.f. power was increased to 160W, triangular grain structure occurrence was seen and root mean square (RMS) was changed from 5.9 nm to 16.8 nm. Optical transmission measurement results showed average transmittance of the thin films was above 82% in the visible spectrum. Moreover, electrical resistivity were measured approximately 10(-3) Omega cm by using four point probe technique. Figure of merit (FOM) for the ZnO thin film reached a maximum as 97 x 10(4) (Omega cm)(-1) for the 165 W r.f. power. The results showed that the small changes in the r.f. power have great importance in ZnO thin film deposition at room temperature conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Atomic force microscopy; High resolution transmission electron microscopy; X-ray diffraction; r.f. Magnetron sputtering; Zinc oxide; OPTICAL-PROPERTIES; ELECTRICAL-PROPERTIES; AL FILMS; DEPOSITION TEMPERATURE; RF POWER; MAGNETRON; TRANSPARENT; DEPENDENCE; PHOTOLUMINESCENCE; CRYSTALLINITY; Crystallography; Materials Science; Physics